Efektivitas E-Rohani dalam Membentuk Integritas Personel Polres Minahasa Utara - Wolter Junaedi Nurhamidin; Hawin Fitriyani (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2026)
This study aims to analyze the effectiveness of e-Rohani in shaping the integrity of personnel at the North Minahasa Police Resort. The study employs a quantitative approach with an evaluative and associative design. The research sample consists of 72 personnel who actively participate in coaching through e-Rohani. Data were collected through questionnaires, documentation, and supporting interviews, then analyzed using descriptive and inferential statistics. The results show that the implementation of e-Rohani is in the high category with an average score of 4.16, while personnel integrity is also in the high category with an average score of 4.11. Correlation analysis indicates a strong positive relationship between e-Rohani and personnel integrity with an r value of 0.672 and a significance level of 0.000. The results of simple linear regression show that e-Rohani has a positive and significant effect on personnel integrity, with a t-value of 7.145 which is greater than the t-table value of 1.999. The coefficient of determination of 45.2 percent indicates that e-Rohani makes a substantial contribution to strengthening responsibility, discipline, ethical compliance, and value consistency among personnel. Therefore, e-Rohani is proven to be effective as a digital-based spiritual development instrument in supporting the strengthening of police personnel integrity.